Dinâmica de formação de biofilmes por Salmonella Enteritidis de surtos de doenças transmitidas por alimentos - Oliveira, Amauri Picollo de (2016)
Salmonella Enteritidis (SE) is able to form biofilms and remain in the processing environment, with bigger chance of transmission to processed foods, representing major risks to food safety and may lead to outbreaks of foodborne illness, and is extremely relevant to public health. The food industry has various materials which compose the surfaces of food processing equipment. Although perform the routine hygienisation procedures, there is a possibility of aggregation organic material and higher probability adhesion of pathogenic microorganisms in these areas, recognized sources of microbial contamination, and increased resistance to sanitizers, worrying feature of microbial biofilms. Thus, we evaluated the SE ability to form biofilms on different surfaces, mimetizing the pre-operational and operational hygiene procedures to remove them from the surfaces of food contact. Therefore, surfaces of polyurethane, polyethylene and stainless steel, commonly used in slaughterhouse, were used as test samples immersed in Salmonella Enteritidis cultures and incubated at 3±1°C, 9±1°C, 25±1ºC, 36±1°C and 42±1°C. Incubation times were 0, 4, 8, 12 and 24 hours, simulating the periods of operational and pre-operational hygiene in poultry slaughterhouses. Tests were performed using sterilized water heated at 45°C and 85°C, in which the samples remained immersed for 3 minutes, and sanitizers solutions with 0.5% peracetic acid and 1% quaternary ammonium in which the samples remained immersed for 5 minutes, simulating operational and preoperational hygiene used in poultry slaughterhouses. Bacterial adherence showed that both SE adhered in stainless steel, polyethylene and polyurethane. As regards the exposure temperatures, SE 24 and SE 69 adhered to 3°C, 9°C, 25°C, 36°C and 42°C, increasing the adhesion with increase in temperature. There was no statistical difference in the formation of biofilms after 4, 8, 12 and 24 hours of incubation in each sample. Peracetic acid has proved to be the better treatment for the removal of biofilms. Quaternary ammonia and water to 85ºC removed the biofilm, but with less effective compared with the peracetic acid. Overall, the results demonstrated that these materials used in the food industry, results in the adherence of SE in different environmental conditions. Emphasizes the formation of biofilms in refrigeration temperature, especially at 3°C, first described by our research group as possible for growth of Salmonella Enteritidis on these surfaces. Our results are important for the development of strategies to control Salmonella Enteritidis biofilms and may assist the poultry industry to have a better understanding of the actual conditions of the slaughterhouses, leading to an improvement of the hygienic conditions of these establishments.